Advances in airborne and ground geophysical methods for uranium exploration (IAEA nuclear energy series ;, 2013)
"Due to growing global energy demand, many countries have seen a rise in uranium exploration activities in the past few years, and newly designed geophysical instruments and their application in uranium exploration are contributing to an increased probability of successful discoveries. This publication highlights advances in airborne and ground geophysical techniques and methods for uranium exploration, succinctly describing modern geophysical methods and demonstrating their application with examples."--Publisher's description.